THE EFFECTIVENESS OF USING AUDIO BOOK IN TEACHING LISTENING SKILL OF EIGHTH GRADE STUDENT - Nurrahman, Kemas Muhammad Rizki; Rositasari, Tri; Larasati, Finza; Yuliani, Sri (Universitas Muhammadiyah Palembang, 2023)
The objective of this research was to find out whether teaching listening using audiobook in listening significant or not. The method used in this research was true experimental method. The population of this research was all the tenth grade students of SMP Muhammadiyah 1 Palembang. The total number of population was 90 students. The samples took out were 60 students from 90 students by using non-probability sampling method. They divided into the experimental and control group. The data were collected by using written test, those were pretest and posttest. The result of the test was analyzed by independent sample t-test. The analyses provide that teaching listening using audiobook on listening help students to improve their listening skill. The mean in posttest of experimental group was 77.17, it was higher than the mean posttest of the control group which was 64.47. The result of T-Test obtained significance (sig. 2 tailed) was 0.001, which less or lower than 0.05. Since the sig. 2 tailed was less than 0.05, so the null hypothesis Ho was rejected and the alternative hypothesis Ha was accepted. It means that there was significant difference on students’ listening taught using audiobook than those who are not